PERAN SERTA SISWA DALAM PENGEMBANGAN USAHA KESEHATAN SEKOLAH (UKS) DI SDN NGRINGIN DEPOK SLEMAN YOGYAKARTA - Asda, Patria (Jurnal Kesehatan Masyarakat, 2016)
ABSTRACT Every school has an important role to create and improve the health of students through Student Health Units can make an effort to create an environment "Healthy Schools" (Health Promoting School/ HPS). Efforts to develop a healthy school needs to be socialized and well done through the ministry of health (health services) that are stable and adequately supported by other related sectors, such as the participation of communities, businesses, and mass media. The study was descriptif analitics. The samples in this study were students of class V and VI SDN Ngringin by 74 respondents. Research tool used was a questionnaire, and analysed using descriptive analysis techniques. The results showed the level student participation is 97,3%. The result of analisis of the questionarre found the students activities about students participation in development of Student Health Units in SDN Ngringin Keywords: participation, Student Health Units